A review of carbohydrate supplementation approaches and strategies for optimizing performance in elite long-distance endurance - Cao, W.; He, Y.; Fu, R.; Chen, Y.; Yu, J.; He, Z. (Nutrients, 2025)
Carbohydrate supplementation is a common practice among endurance athletes participating in long-distance competitions. However, glycogen storage regulation, in-competition blood glucose levels, and their relationship with athletic performance are influenced by multiple factors. This review summarizes the recent research progress on carbohydrate supplementation, addressing its applications in the pre-, during-, and post-competition phases. It explores variables that influence the effectiveness of carbohydrate supplementation and provides a summary of strategies, based on six key aspects: carbohydrate properties, multi-nutrient interactions, gastrointestinal function, individual differences (such as age and gender), environmental conditions, and psychological factors. The combination of different types, ratios, and concentrations of carbohydrates has been demonstrated to enhance the efficiency of carbohydrate digestion and absorption. The synergistic combination of protein, sodium, and caffeine intake demonstrates enhanced efficacy in carbohydrate supplementation strategies. Gastrointestinal tolerance training for carbohydrate supplementation has been identified as an effective measure to alleviate gastrointestinal discomfort during high-dose carbohydrate intake. The adjustment of the carbohydrate-to-fat ratio and the type of carbohydrate intake has been found to mitigate the impact of gender and menstrual cycles on glycogen storage and substrate utilization. Modifying the timing of glycogen storage and regulating the concentration and temperature of carbohydrate solutions during competition have been demonstrated to facilitate coping with the elevated energy expenditure and metabolic substrate shift from fat to carbohydrates, triggered by a combination of environmental and psychological factors, including special environmental and climatic conditions (e.g., high altitude, high temperature, high humidity, and cold) and emotional states (e.g., pre-competition stress and anxiety during the competition). To achieve precise carbohydrate supplementation for athletes in major events under various competitive environments, it is necessary to quantitatively assess the effects of carbohydrate supplementation, supported by mechanistic studies. This can be achieved by utilizing wearable devices to monitor the entire competition, coupled with data collection technologies, such as high-throughput profiling. Furthermore, emerging data analytics techniques, such as machine learning and causal inference, should be leveraged to refine supplementation strategies.